Landscape structure coupled to instream features shape freshwater biodiversity in Cerrado agricultural landscapes - Santos, Juliana Silveira dos; Hasui, Erica; Teresa, Fabrício Barreto; Nabout, João Carlos; Machado, Karine Borges; Martello, Felipe; Vieira, Ludgero Cardoso Galli; Collevatti, Rosane Garcia (Perspectives in ecology and conservation, 2025)
[Display omitted] •Landscape structure and instream features affect freshwater biodiversity at fine and large spatial scales.•Microcrustaceans have been favored by landscapes dominated by crops and pastures.•Landscape changes are favoring some biological groups which can lead to freshwater biotic homogenization.•The unsustainable expansion of agriculture and livestock activities are compromising freshwater biodiversity and water quality. Freshwater biodiversity is threatened at global scale, thus, understanding how it responds to anthropogenic interferences is critical, especially in regions where human disturbances have quickly altered natural ecosystems. Here, we address the effects of landscape structure in Brazilian Cerrado on freshwater community diversity of phytoplankton, periphyton, zooplankton and fish, and instream’s features (physicochemical and biological indicators of water quality, and water velocity), and the effects of instream’s features on freshwater community diversity. We analyzed the data at different spatial scales (50, 100, 150, and 200 m, and watershed level), using structural equation modeling. We found that percentage of native vegetation (%NV) at watershed level explained Cladocera’s abundance and Shannon-wiener with a negative relationship. Landscape compositional heterogeneity (SHDI) at 200 m explained Periphyton abundance with a positive relationship. %NV at 50 m explained dissolved oxygen with a positive relationship. Total coliforms explained Cladoceras’s abundance with a positive relationship. Conductivity explained Cladocera’s abundance and richness with a negative relationship. Our findings show that landscape changes are favoring some biological groups, which can lead to freshwater biotic homogenization. Thus, the unsustainable expansion of agriculture can compromise freshwater biodiversity and water quality in Cerrado.